Virtual Laboratory Media Training at Muhammadiyah Langsa High School in Supporting The Independent Curriculum - Hendri Saputra; Nursamsu Nursamsu; Hasby Hasby; Elfrida Elfrida (Pascasarjana Universitas Mataram, 2023)
Learning media has a very close relationship with the independent curriculum. As a curriculum that gives students the freedom to choose and determine the direction of their learning, an independent curriculum requires appropriate learning media to support and facilitate this freedom. The learning media used in this service activity is virtual laboratory media as a learning media that can be a solution to the problem of learning loss. The aim of this service activity process is to provide an explanation that is presented by presenting material about the importance of technology in learning, introducing examples of technology that can be used in the virtual practicum learning process. To carry out training in creating practical learning media based on simulation and animation media in accordance with the materials contained in science subjects which can be used in online science practicum learning. Carrying out training on creating a YouTube channel to uploading materials and getting YouTube links for materials that have been uploaded on the channel to sharing YouTube links with science teachers through online learning applications used such as Google Classroom. The method used in service activities is the service learning method with 4 activity stages, namely the Investigation Stage, Preparation Stage, Action Stage and Reflection Stage. The results of community service activities at SMA Muhammadiyah Langsa which were given to teachers and students had a positive impact on the use of virtual laboratory media applications to support the Merdeka curriculum